1939
DOI: 10.1192/bjp.85.359.1163
|View full text |Cite
|
Sign up to set email alerts
|

Feeding in Infancy and Subsequent Psychological Difficulties

Abstract: In many theories concerning the development of psychological illness, stress has been laid upon the difficulties encountered during the earliest period of life. The problems of feeding in infancy and early childhood have, in particular, been believed to colour if not actually to determine certain neurotic and psychotic behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1951
1951
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…One study, 10 however, used both health records and maternal interviews, and found inconsistent recordings in the health record. 10 This type of inconsistency may lead to inaccurate classification in the other studies 4,5,11,12,20,23,30 that relied on historical records, but the use of archived data did not address whether feeding information was always available for every child.…”
Section: Quality Of the Feeding Datamentioning
confidence: 96%
See 1 more Smart Citation
“…One study, 10 however, used both health records and maternal interviews, and found inconsistent recordings in the health record. 10 This type of inconsistency may lead to inaccurate classification in the other studies 4,5,11,12,20,23,30 that relied on historical records, but the use of archived data did not address whether feeding information was always available for every child.…”
Section: Quality Of the Feeding Datamentioning
confidence: 96%
“…Only 9 (23%) 1,14,16,29,30,34,38,40,58 of 40 met all 4 criteria regarding the quality of feeding data; 8 were full-term birth cohorts. For example, a study with high-quality feeding data 29 specified the breastfed groups as those that "mostly breastfed;" feeding status was determined at multiple times (at birth, 6 weeks, and 3, 6, 12, and 18 months); information was obtained by interviewing the mother at each of those times; and the duration of breastfeeding was more than a month in the "breastfed" group.…”
Section: Quality Of the Feeding Datamentioning
confidence: 99%
“…The EPVT (Brimer and Dunn 1962), originally adapted from the American Peabody Picture Vocabulary Test, consisted of a series of 56 sets of four pictures. This selfcompletion index of the mother's psychological state was obtained using the 24item Malaise Inventory (Rutter et al 1970), developed from the Cornell Medical Index Health Questionnaire (Brodman et al 1952). The test proceeded with words of increasing difficulty until the child made five mistakes in a run of eight items.…”
Section: Methodsmentioning
confidence: 99%
“…There have been many studies on the interrelationships between breast or bottle feeding and the child's subsequent behaviour (Hoefer and Hardy 1929, Pearson 1931, Childers and Hamil 1932, Hill 1937, Rogerson and Rogerson 1939, Peterson and Spano 1941, Masler and Szilagyi-Kessler 1946, Holway 1949, Orlansky 1949, Sewell and Mussen 1952, Heinstein 1963, Silva et al 1978. The earlier studies present a contradictory picture; some showed a relationship between breast feeding and less behaviour problems (Hoefer and Hardy 1929, Pearson 1931, Childers and Hamil 1932, Hill 1937, Rogerson and Rogerson 1939, Maslow and Szilagyi-Kessler 1946, Holway 1949 and some showed no effect (Peterson and Spano 1941, Orlansky 1949, Sewelland Mussen 1952, Heinstein 1963, Silva et al 1978. Among those showing apparent benefit, the required optimal duration of breast feeding varied from linearly increasing benefit (Rogerson andRogerson 1939, Holway 1949) to a middle range (four to 11 months)-the extremes being associated with unfavourable outcome (Hoefer and Hardy 1929, Pearson 1931, Hill 1937)-to areverse curvilinearpattern, with best behaviour being associated with no or only short-term breast feeding (less than one month) or longer than 11 months (Childers andHamil 1932, Maslow andSzilagyi-Kessler 1946).…”
mentioning
confidence: 99%
“…It has also been shown that weaning problems can be correlated with the amount of time spent sucking previously, which is generally more in breast fed infants (Sears & Wise 1950). Even at 7 years of age, poor appetite and feeding problems were found to be associated with prolonged breast feeding and the late introduction of chewable foods (Rogerson & Rogerson 1939).…”
Section: Discussionmentioning
confidence: 99%